Alternative Negotiating Conditions and the Choice of Negotiation Tactics: A Cross-cultural Comparison - Volkema, Roger J. (Journal of business ethics, 2002)
The growth in international trade in recent years necessitates a better understanding of customs and expectations in cross-cultural negotiations. While several researchers have sought to examine and detail the similarities and differences between select countries, their data have generally been obtained under neutral or unspecified negotiating conditions. However, issue importance, opponent (prowess, ethical reputation), and context (location, confederate awareness, urgency) can play a significant role in the use of negotiating tactics. This paper describes a study comparing the perceptions of one hundred and forty-two current and future business professionals from two emerging trade partners, Brazil and the United States, regarding the appropriateness and likely use of five categories of negotiation tactics under seven challenging or unfavorable negotiating conditions commonly faced by negotiators. The results indicate an overall conditional effect for both attitudes (perceived appropriateness) and intentions (likelihood of use). In addition, while no significant difference in perceived appropriateness was found due to country, there were differences in likely use due to country for six conditions-behaviors.